(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This paper presents the influence of free and forced vibrations on thin the plate of (50cm length, 30 cm width, 0.5 mm thickness), made from steel 37 with two types of supports, firstly when it is fixed from two sides and other sides are free (CFCF) and secondly when one end of the plates is fixed and the other three sides are free (CFFF). As well as, this work studies the mode shapes and natural frequency of the plate. When the frequency is applied on the plate with different magnitudes (4,6,8,10) Hz, the amplitude of vibration decreased more than free vibration and when the frequency increased, the amplitude of the vibration increased or decreased but still less then at free vibration depending on the type of support. Ansys and MATLAB software were used to find the natural frequency and to enter the boundary conditions of the plate for comparison purposes.